Estilos políticos y orientación tecnocrática bajo los gobiernos de Lagos y Bachelet - Silva, Patricio (Revista de Sociología, 2007)
This article explores the ways in which Presidents Lagos and Bachelet have dealt with the technocratic phenomenon within their respective governments. For this purpose, special attention is given to the political styles characterizing both presidents and the manner in which these styles have facilitated or obstructed the functioning of technocratic groups within governmental circles. As it is argued, the attitude adopted by both leaders vis-à-vis the presence of technocratic groups within their governments is largely conditioned by the type of relation established between the presidents and the supporting political parties. In addition to this, a sordid clash between politicians and technocrats for power and influence can be observed. President Lagos always distrusted the technocracy. He only made strategic use of it in order to lehis cgitimate onduction of the country's economy towards entrepreneurial groups and the international financial community. On the other hand, President Bachelet will be forced to seek support from the 'Expansiva' technocrats due to her problematic relation vis-à-vis the leaders of the Concertación's political parties.